Administrative regulation-informed analysis of the developmental path of national volume-based procurement to improve drug accessibility in China - Lu, Songxin; Liu, Xiangdong; Huang, Zhengzong; Zhou, Zhiheng; Feng, Zehua (Frontiers in Public Health, 2024)
The procurement of medicines via China's national volume-based procurement (NVBP) necessitates collaboration among various entities. This paper highlights the legal significance of the engagement of pharmaceutical companies, hospitals, and the National Healthcare Security Administration (NHSA) in a thorough analysis of the evolutionary game model to improve drug accessibility. We conducted a numerical simulation using MATLAB to develop an evolutionary game model involving these three participants in NVBP. According to our findings, the final evolutionary stabilization strategies are pharmaceutical companies actively participating, hospitals using bid-winning medicines, and the NHSA implementing a low-intensity intervention. The study reveals that the evolutionary outcomes for hospitals and pharmaceutical companies are significantly affected by factors such as NHSA's subsidy level and pharmaceutical companies' level of participation. However, NHSA's decision-making process is less influenced by these factors. From a legal perspective, the successful implementation of NVBP, ensuring fairness and legality, requires adherence to relevant policies and regulations. The NHSA should employ statutory incentives and regulatory methods in formulating and adjusting NVBP policy to enable pharmaceutical companies, China's National Volume-Based Procurement 2 hospitals, and the NHSA to exercise their rights rationally within the legal framework of the game process.